Documenting and exploiting software feature knowledge through tags - Seiler, Marcus; Paech, Barbara (Proceedings SEKE 2019, 2019)
We developed an approach and tool TAFT to document feature knowledge in ITS and IDE continuously. TAFT uses feature tags to indicate relations between feature descriptions, requirements, work items, and source code.